2013
DOI: 10.1016/j.jmb.2013.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Steric Complementarity in the Decoding Center Is Important for tRNA Selection by the Ribosome

Abstract: Accurate tRNA selection by the ribosome is essential for the synthesis of functional proteins. Previous structural studies indicated that the ribosome distinguishes between cognate and near-cognate tRNAs by monitoring the geometry of the codon-anticodon helix in the decoding center using the universally conserved 16S rRNA bases G530, A1492 and A1493. These bases form hydrogen bonds with the 2’-hydroxyl groups of the codon-anticodon helix, which are expected to be disrupted with a near-cognate codon-anticodon h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 56 publications
4
24
1
Order By: Relevance
“…These results are in line with earlier studies, reporting a 50–75%-fold decrease at distinct steps of translation (e.g. A-site tRNA binding or EF-Tu GTPase activation, respectively) when introducing single deoxy-nucleotides; an almost complete translational inhibition at the modified codon was observed introducing two or more deoxy-nucleotides ( 45 , 46 ).…”
Section: Resultssupporting
confidence: 93%
“…These results are in line with earlier studies, reporting a 50–75%-fold decrease at distinct steps of translation (e.g. A-site tRNA binding or EF-Tu GTPase activation, respectively) when introducing single deoxy-nucleotides; an almost complete translational inhibition at the modified codon was observed introducing two or more deoxy-nucleotides ( 45 , 46 ).…”
Section: Resultssupporting
confidence: 93%
“…This longstanding concept has been difficult to demonstrate directly until recently, when the first structural evidence for errors in replication via GÁT and CÁA mismatches with Watson-Crick geometry was procured [60][61][62]. Other non-structural experimental findings also demonstrate that steric or shape complementarity, rather than H-bonding, is paramount in replication and translation [63][64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…What has been less understood is the extent to which the structure of the mRNA itself is important for this process. Nonetheless, biochemical studies of the role of the mRNA ribose backbone during decoding showed that the substitutions of A-site 2′-OH residues with deoxy or fluoro groups had minimal impact on tRNA selection (37). This is in contrast to structural studies, which showed that the hydroxyl groups are important for A-minor interactions with the decoding center nucleotides (31,32).…”
Section: Significancementioning
confidence: 84%
“…However, recent structural studies from a different group suggested that the hydrogen bonding was identical for both cognate and near-cognate codons (38) and that accuracy originates from energetic penalties associated with base-pair mismatches being forced to adopt a Watson-Crick base-pair geometry. Previous biochemical studies by Simpson and colleagues (37) explicitly addressed the role of the 2′-OH groups of the A site in decoding. Interestingly, single substitution of any of the 2′-OH groups by a deoxy only marginally affected peptide-bond formation.…”
Section: Phosphorothioate Substitutions At the Interface Of The P Andmentioning
confidence: 99%